Analisis Teks pada Buku Pelajaran Bahasa Indonesia Kelas X Terbitan Kemdikbud Edisi Revisi Tahun 2017 - Numertayasa, I Wayan; Selamet Kumara Priantara, I Komang Gede (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to conduct a text analysis on Indonesian language textbooks in Grade X by focusing on (1) Language Use in Indonesian Language Textbooks in Grade X, (2) Conformity of Indonesian Language Textbooks in Grade X to the 2013 Curriculum, (3) Conformity of Indonesian Language Textbook Discourse to Strengthening Character Education for Grade X Students, (4) Impact of Indonesian Language Textbooks on Learning for Grade X Students. The method in this research is descriptive qualitative research method with critical discourse analysis approach. The subject of this research is the Indonesian Language textbook Grade X for SMA/SMK, published by the Ministry of Education and Culture in the 2017 revised edition. The results showed that from (1) language use, (2) conformity with the 2013 curriculum, (3) conformity of discourse with strengthening character education, (4) the impact of textbooks on student learning is included in the good category, feasible, and in accordance with the level of understanding of students. In accordance with these findings, it is expected that the government and teachers should work together to develop and improve the quality of Indonesian language learning books to make them more interesting in accordance with the times, relevant, easy for students to understand